Technology-Based Counselor Training: Impact on Competence and Intervention Effectiveness - Dhiana Setyorini; Dian Aby Restanty; Ariefa Quinta Hanum (Yayasan Adra Karima Hubbi, 2024)
The increasing complexity of mental health issues has emphasized the need for continuous professional development for counselors. Traditional training methods, limited by time and location, may not fully equip counselors with necessary skills. Technology-based training, such as online courses and virtual simulations, offers new opportunities to enhance counselor competence and intervention effectiveness. However, limited research exists on the impact of these methods. This study evaluates the effectiveness of technology-based training in improving counselor skills and client outcomes. A mixed-methods design was used, involving 100 counselors: 50 received traditional in-person training, and 50 received technology-based training through an online platform. Quantitative data were collected via pre- and post-training assessments and client satisfaction surveys, while qualitative data were gathered through interviews and focus groups. Results showed a 30% increase in competence scores for counselors receiving technology-based training, compared to a 15% increase for those in traditional training. Clients of technology-trained counselors reported higher satisfaction and perceived effectiveness of interventions. Qualitative feedback highlighted greater flexibility, interactive experiences, and immediate feedback in digital training, leading to higher engagement and knowledge retention. The study concludes that technology-based training effectively enhances counselor competence and outcomes, offering a flexible and interactive approach for continuous professional development.